Islamic reform in South Asia - Filippo Osella (ed.); Caroline Osella (ed.) (New York: Cambridge University Press, 2013)
"Discusses contemporary Islamic reformism in South Asia in some of its diverse historical orientations and geographical expressions"--Provided by publisher.
Keywords: Islamic History Asia; Islamic Renewal South Asia; Islam South Asia; Islam; Religion